2017
DOI: 10.1016/j.ebcr.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical management of New Onset Refractory Status Epilepticus (NORSE) presenting with gelastic seizures in a 3 year old girl

Abstract: Gelastic seizures (GS) are typically associated with hypothalamic hamartomas and present during childhood. However it is now known that GS can be found in focal epilepsies arising from other regions in the brain, including mesial and neocortical frontal, temporal and parietal regions.GS have rarely been described as the presenting manifestation of New Onset Refractory Status Epilepticus (NORSE). In this article we describe a previously healthy 3-year-old who presented with an explosive onset of GS that were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
6
0
7
Order By: Relevance
“…Similarly, Hu et al (2011) described a teenager with drug-refractory GS that resolved completely following resection of a focal cortical dysplasia. Marashly et al (2017) reported an interesting case of a three-year-old female who presented with GS in the setting of new-onset refractory status epilepticus. PET and SEEG identified the SOZ in the right superior frontal gyrus.…”
Section: Extra-hypothalamic: Frontal-onset Gsmentioning
confidence: 99%
“…Similarly, Hu et al (2011) described a teenager with drug-refractory GS that resolved completely following resection of a focal cortical dysplasia. Marashly et al (2017) reported an interesting case of a three-year-old female who presented with GS in the setting of new-onset refractory status epilepticus. PET and SEEG identified the SOZ in the right superior frontal gyrus.…”
Section: Extra-hypothalamic: Frontal-onset Gsmentioning
confidence: 99%
“…Syndrom je charakterizován refrakterními epileptickými záchvaty bez prokazatelné aktivní strukturální, toxické nebo metabolické příčiny. Typicky se NORSE prezentuje jako super-refrakterní status epilepticus, ale toto kritérium není podmínkou dia gnózy [1][2][3]. Ve většině případů NORSE předchází mírné febrilní onemocnění [4].…”
Section: úVodunclassified
“…Jedná se o zřídkavý, akutní, potenciálně fatální epileptický syndrom, kterému předchází febrilní infekt. Latence mezi febrilním infektem a manifestaci RSE je uváděna v rozmezí 24 h až 2 týdnů [2]. Postihuje děti ve věku 3-15 let s predominancí chlapců [2].…”
Section: Etiologie a Epidemiologické Charakteristikyunclassified
See 2 more Smart Citations